Analisis Kinerja Keuangan pada Perusahaan Daerah Air Minum Kota Makassar - Ratna Sari (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2022)
The purpose of this study is to determine and describe the development of PDAM performance from a financial aspect based on the Decree of the Minister of Home Affairs No. 47 of 1999. Data analysis technique is a way used to process research data in order to prove a hypothesis. After the data collected in this study is collected, the data must be analyzed so that the problem in the study is solved and the research objectives are achieved. This study used non-statistical quantitative analysis. From the results of the assessment of the financial performance of PDAM Makassar City in 2014-2017, it was found that 1) Financial performance from 2014-2017 was good. Financial performance with the highest value (50) was in 2015 while the lowest value in 2014 was (37), and in 2016 financial performance was (45) and in 2017 financial performance was (41). 2) Overall, out of 10 (ten) indicators, there are 5 (five) indicators that have performed well, namely the ratio of long-term debt to equity, the ratio of total assets to total debt, the ratio of productive assets to water sales, the period of collection of receivables, and the effectiveness of collection, the ratio of operating expenses to operating income, the ratio of operating profit before depreciation expense to principal installments and interest due. 3) While the indicator that requires attention is the ratio of current assets to current debt.